Multiple intussusceptions after blunt abdominal trauma in a 9-year-old boy: A case report and literature review. (April 2022) - Lee, Shin Ae; Youn, Joong Kee; Chang, Ye Rim
Abstract: Traumatic intussusception is exceedingly rare. According to the existing literature, most cases are treated surgically. However, the treatment and prognosis of traumatic intussusception are not well understood, and more research is needed to determine the most beneficial treatment options. Multiple intussusceptions were found on a computed tomography scan of a 9-year-old boy with multiple severe traumatic injuries resulting from a car accident while riding an electric scooter. Conservative management was performed, and spontaneous reduction was successfully achieved without complications. This is the first reported case where multiple traumatic intussusceptions in a pediatric patient were managed without surgical intervention. Thus, traumatic intussusception of varied quantity and quality might be managed conservatively, yielding spontaneous resolution with the prerequisites of stable vital signs and no evidence of intestinal ischemia or perforation.